Towards the use of Blockchain Technology in SEI, a Brazilian Electronic Document and Process Management Tool - Gottschalg-Duque, Claudio (Anais do Colóquio em Blockchain e Web Descentralizada (CBlockchain); 2024: Anais do II Colóquio em Blockchain e Web DescentralizadaDO - 10.5753/cblockchain.2024.3036, 2024)
The Sistema Eletrônico de Informação (SEI) is a Brazilian system that manages electronic documents and processes, promoting administrative efficiency and transparency. The SEI is part of the National Electronic Process Initiative (PEN), and its implementation contributes to modernization and efficiency in Brazilian public administration. Blockchain technology with Smart Contracts can help the Brazilian Federal Government avoid security and technology problems. By addressing these challenges and leveraging the inherent benefits of blockchain technology, the Brazilian government can unlock new opportunities for improving the reliability, security, and efficiency of its information management processes within the SEI.